Intergenerational mobility in Korea - Soobin Kim (IZA Journal of Development and Migration, 2017)
This study investigates intergenerational earnings mobility in Korea for sons born between 1958 and 1973 and compares Korea's mobility to that of other nations. It uses data from the Korea Labor and Income Panel Study and the Household Income and Expenditure Survey conducted by the Korean National Statistics Bureau. Since no single Korean dataset includes information on both sons' and their fathers' adult earnings, this study follows the two-sample approach previously applied in Korea by Ueda (J Asian Econ 1-22, 2013), whose estimated intergenerational earnings elasticity is 0.22, and extends the analysis by using fathers' earnings from a more approximal cohort. The estimate of around 0.4 is similar to estimates for some already developed countries and smaller than typical estimates for recently developing countries.
Keywords: J6; J31; 330; Intergenerational earnings mobility; Generated regressor; Two-sample estimation